Students' Necessities for Acquiring English as a Second Language in Vocational High Schools - Andi, Andi Eka Prima (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2024)
SLA is a mandatory subject studied in the educational environment, particularly for students in the Engineering Class (SEC). Engineering students have recently concentrated solely on common textbooks printed in English. Therefore, it does not undoubtedly aid in the development or promotion of understanding materials for English engineering purposes (EEP) among students. Naturally, identifying English materials that prioritize the demands of the students is essential when creating materials for specific objectives, like engineering students. Based on this, the survey and analysis approach are used to identify the textbooks by incorporating teachers and students in the data collection process. In this instance, it is reasonable to assume that students will learn the things to assist them become proficient in English for their future employment.